Eco-friendly, solution-processed In-W-O thin films and their applications in low-voltage, high-performance transistors. Issue 20 (18th April 2016) - Liu, Ao; Liu, Guoxia; Zhu, Huihui; Shin, Byoungchul; Fortunato, Elvira; Martins, Rodrigo; Shan, Fukai
Abstract : Eco-friendly IWO thin films are fabricated via a low-cost solution process and employed as channel layers in thin-film transistors. Abstract : In this study, amorphous indium-tungsten oxide (IWO) semiconductor thin films were prepared by an eco-friendly spin-coating process using ethanol and water as solvents. The electrical properties of IWO thin-film transistors (TFTs), together with the structural and morphological characteristics of IWO thin films, were systematically investigated as functions of tungsten concentration and annealing temperature. The optimized IWO channel layer was then integrated on an aqueous aluminum oxide (AlO x ) gate dielectric. It is observed that the solution-processed IWO/AlO x TFT presents high stability and improved characteristics, such as an on/off current ratio of 5 × 10 7, a field-effect mobility of 15.3 cm 2 V −1 s −1, a small subthreshold slope of 68 mV dec −1, and a threshold voltage shift of 0.15 V under bias stress for 2 h. The IWO/AlO x TFT could be operated at a low voltage of 2 V, which was 15 times lower than that of conventional SiO2 -based devices. The solution-processed IWO thin films synthesized in a green route would be promising candidates for large-area and high-performance low-cost devices.